2021
DOI: 10.1371/journal.pone.0249379
|View full text |Cite
|
Sign up to set email alerts
|

Single START-domain protein Mtsp17 is involved in transcriptional regulation in Mycobacterium smegmatis

Abstract: Tuberculosis caused by the pathogen Mycobacterium tuberculosis (MTB), remains a significant threat to global health. Elucidating the mechanisms of essential MTB genes provides an important theoretical basis for drug exploitation. Gene mtsp17 is essential and is conserved in the Mycobacterium genus. Although Mtsp17 has a structure closely resembling typical steroidogenic acute regulatory protein-related lipid transfer (START) family proteins, its biological function is different. This study characterizes the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The biological function of Rv0164 is unknown to date. However, several studies have investigated its homolog in M. smegmatis, MSMEG_0129 (Zheng et al, 2017(Zheng et al, , 2018Zhou et al, 2020Zhou et al, , 2021, which shares 59% identity with Rv0164. These proteins are classified as polyketide aromatase/cyclase family members of the steroidogenic acute regulatory protein-related lipid transfer (START) domain superfamily based on sequence alignment (Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological function of Rv0164 is unknown to date. However, several studies have investigated its homolog in M. smegmatis, MSMEG_0129 (Zheng et al, 2017(Zheng et al, , 2018Zhou et al, 2020Zhou et al, , 2021, which shares 59% identity with Rv0164. These proteins are classified as polyketide aromatase/cyclase family members of the steroidogenic acute regulatory protein-related lipid transfer (START) domain superfamily based on sequence alignment (Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nutrient deficiency led to the down-regulation of MSMEG_0129 and Clp2 and the up-regulation of CarD. A recent study mapped the transcriptional profile of strains with the decreased expression of msmeg_0129 and found numerous genes involved in cell wall biosynthesis and metabolism to be differentially expressed, leading the authors to propose that MSMEG_0129 might coordinate signal transfer during stress responses ( Zhou et al, 2021 ). It remains to be confirmed whether the same is true for Rv0164.…”
Section: Discussionmentioning
confidence: 99%
“…This function is predicted to be active in the Rv1546 dimer. Although the functions of START domain proteins in M. tuberculosis remain undetermined, some research papers showed that the proteins are essential for bacterial growth and survival (Zhou et al, 2020(Zhou et al, , 2021. Therefore, in consideration of structural features and homologs of Rv1546, Rv1546 has a potential to be a novel drug target against TB.…”
Section: Discussionmentioning
confidence: 99%
“…In prokaryotes, the START domain is found in polyketide ARO/CYC proteins. Although plant and mammalian proteins containing the START domain have been shown to function in lipid binding or the modulation transcription factor activity (Schrick et al, 2014), these functions were not well known in prokaryotes until recent studies elucidated their transcriptional regulatory function in M. tuberculosis (Zheng et al, 2018;Zhou et al, 2021). In addition to this native property, the domain-swapped dimer structure might confer a new function, such as ribonuclease activity, on Rv1546.…”
Section: Discussionmentioning
confidence: 99%